Martin Heidegger, Reiner Schürmann. Destruction of theo-onto-anthropology and post-humanism - Gonzalo Díaz Letelier (Resonancias: Revista de Filosofía, 2019)
Reiner Schürmann's work suggests an anarchic and atheological theoretical praxis to think politics at the time of the technical consummation/exhaustion of the principial metaphysics: the destruction of ontotheological political metaphysics (pars destruens) and the opening of non-ontotheological politics (pars construens) to inhabit in a non-sacrificial way in the time of anarchy. In this essay we address the destructive part of his analytic, first providing some indications on the Schürmann's dismantling of the ontotheological structure of metaphysics from his reading of Heidegger: his phenomenological interpretation of “truth” as hegemonic fantasm (phantasmatic and exceptional hermeneutical-normative nómos). Then we attempt to expose the logic of the government involved in the nomical character of ontotheological political economy –the conversion of the singular/plural in particular/universal– through a reference to Aristotle's metaphysics, specifically to his doctrine of categories and the finalistically mediated relationship between potentiality and actuality. The horizon of this essay is the consideration of a metaphysical-political bifurcation in phenomenology, regarding to spectrality, the question of the principial metaphysical foundation of inhabiting and the humanism that derives from it.